PENGARUH KUALITAS PENERAPAN SIA, PEMANFAATAN DAN KEPERCAYAAN TEKNOLOGI INFORMASI PADA KINERJA KARYAWAN - ari kasandra, ayu; Juliarsa, Gede (E-Jurnal Akuntansi, 2016)
The Sustainability and success of an organization can be seen from the performance of which is owned by the employees. This studyed aimedds to determined effects the quality of accounting informations system implementation, use of information technology and trust in the information technology employee performance. This research was conducted at the Rural Bank in Tabanan. Samples were taken by purposive sampling technique. The data analysis technique used is multiple linear regression analysis. The results showed that the quality of the application of accounting information systems, information technology utilization and beliefs have a significant effect on the performance of the employee. The presence of employees in the use of technology facilitates data management, data access and improve efficiency. Trust the technology will allow staff to achieve better performance.
Keywords: the quality of the application, technology, employee performance